2021
DOI: 10.1093/ofid/ofab248
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cytomegalovirus-Specific Cell-Mediated Immune Monitoring and Cytomegalovirus Infection in Patients With Active Systemic Lupus Erythematosus Receiving Immunosuppressants

Abstract: Introduction The effects of cytomegalovirus (CMV)-specific cell-mediated immunity (CMI) on CMV infection in patients with autoimmune diseases receiving immunosuppressants have not been explored. Methods Patients with active systemic lupus erythematosus (SLE) were preemptively monitored for clinically significant CMV infection (CsCMVI, defined as plasma CMV DNA loads > 3 log10 IU/mL). CMV-specific CMI was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Its findings show that the risk of CMV reactivation was correlated with QuantiFERON-CMV levels after 1 month of intense immunosuppression. 27 To our knowledge, this is the first publication evaluating SLE patients with CMV infection/disease in a Colombian population. Nevertheless, it has some important limitations to consider.…”
Section: Discussionmentioning
confidence: 94%
“…Its findings show that the risk of CMV reactivation was correlated with QuantiFERON-CMV levels after 1 month of intense immunosuppression. 27 To our knowledge, this is the first publication evaluating SLE patients with CMV infection/disease in a Colombian population. Nevertheless, it has some important limitations to consider.…”
Section: Discussionmentioning
confidence: 94%
“…CMV infection in SLE may present as gastrointestinal bleed, colitis, hepatitis, retinitis, or encephalitis, with a high incidence of pneumonitis. 32 High dose of glucocorticoids, cyclophosphamide, plasma exchange, pancytopenia and concurrent infections have been associated with serious CMV clinical syndrome. High CMV viral loads are associated with the development of CMV infection in patients with SLE.…”
Section: Methodsmentioning
confidence: 99%
“…The manifestations of primary CMV infection are more severe than CMV reinfection or reactivation from latent endogenous virus[ 49 ]. Current guidelines consider D + /R − children to be the most prone to developing severe CMV disease from primary infection[ 50 ].…”
Section: Manifestationsmentioning
confidence: 99%
“…The assay reflects cell-mediated immunity by measuring IFN-γ levels following in vitro stimulation of CD8+ T cells by CMV peptides. The subsequent incidence of CMV disease in immunocompromised patients is significantly lower among those with a positive result than those with a negative result[ 21 , 50 , 63 ]. A multicentre cohort study showed that the positive and negative predictive values of the assay were 0.90 and 0.27, respectively[ 50 ].…”
Section: Investigationmentioning
confidence: 99%
See 1 more Smart Citation